Harnessing Project-Based Learning to Enhance STEM Students' Critical Thinking Skills Using Water Treatment Activity - Opeyemi A. Oyewo; Sam Ramaila; Lydia Mavuru (MDPI AG, 2022)
Water treatment processes are designed to ensure that any pollutant's adverse effects on the environment are reduced to the minimum allowable discharge limit. Water-literate individuals ought to effectively and constantly think about novel hydrologic concepts to improve the quality and sufficiency of water. Socio-hydrological issues remain the main source of water pollution and insufficiency in society. Therefore, effective water management and treatment require societal understanding. The complexity of water issues requires equipping STEM education students with the necessary knowledge to acquire water solution reasoning skills. However, STEM students need meaningful challenges with everyday connections to capture their interest to apply intuitive understanding in project-based learning. Water-related issues such as high turbidity are ubiquitous problems facing communities. This study specifically explored how project-based learning can be harnessed to enhance STEM students' critical thinking skills using water treatment activities. The water treatment activity involved the development of novel products using agricultural wastes for efficient water treatment. The social issues associated with agricultural wastes, especially orange and banana peels in the environment, are too obvious to be overlooked; hence, they were chosen as base materials to develop water treatment products. The study adopted an action research design and involved 12 purposively selected third-year Bachelor of Science students majoring in Chemistry at a South African university. The students were divided into two groups consisting of six participants. The researchers implemented team teaching and invoked students' knowledge of Earth Science, Physics, Chemistry, and Technology to develop and implement laboratory experimental activities and class-based lesson plans. The empirical investigation was underpinned by the Five Steps of Project-Based Learning as the underlying theoretical framework. The chemistry of the processed peels such as particle size and functional groups provided insight into the mechanism responsible for water turbidity reduction. Laboratory experimental results revealed that the turbidity reduction obtained from the use of processed banana peels was higher than the processed orange peels coagulant. However, the performance of both coagulants in turbidity reduction complied with the South African National Standard (SANS241) for drinking water quality.